Reframing accounting disclosure in Indonesia towards IFRS S1 and S2 adoption - Zaki, Ahmad (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study examines how accounting disclosure practices in Indonesia have been conceptually framed within academic scholarship and assesses the extent to which prevailing theoretical orientations engage with the logic embedded in IFRS S1 and IFRS S2. Using a theory driven qualitative analysis of 39 disclosure related articles published in Scopus indexed and ABDC listed journals between 2000 and 2025, the study analyses dominant explanatory frameworks, conceptualisations of disclosure, and engagement with governance, strategy, risk management, and quantitative sustainability metrics. The findings indicate that Indonesian disclosure scholarship remains predominantly anchored in CSR oriented and legitimacy based paradigms, with disclosure frequently conceptualised as a reactive or reputational mechanism. Explicit engagement with forward looking climate-related financial risk, enterprise value implications, and quantified performance indicators appears comparatively limited. At the same time, emerging studies demonstrate incremental diversification, including greater attention to governance structures and carbon performance metrics. Interpreted through an integrative institutional lens combining translation, layering, and complexity perspectives, these patterns reflect gradual conceptual realignment rather than abrupt paradigm replacement. The study contributes to disclosure research by highlighting how academic paradigms evolve during periods of regulatory transition and by positioning scholarly discourse as part of the broader context within which sustainability related financial reporting reforms are interpreted and gradually embedded.